The Relationship between Projects Management Managers’ Competencies and Employees’ Performance of Construction Industry at Gaza Strip - El-sawalhi, Nabil; Lafy, Ramy (International Journal of Sustainable Construction Engineering and Technology, 2021)
Projects managers’ competencies are one of the factors that have the greatest impact on the employees’ performance in construction projects. However, many construction companies appear to give insufficient attention to the issues related to improving the competencies of their project managers. This study investigated the relationship between projects managers’ competencies and employees’ performance under the setting of Gaza construction firms. It aim to identify the competencies required for the contractor’s projects managers that contribute towards the employees’ performance and exploring the most effective methods for developing the construction project manager competencies. A questionnaire survey was used. A total of 110 structured questionnaires were distributed targeting project managers, 94 valid questionnaire to be used for further discussions with a response rate of 85.5%. The results show that the employees’ performance in construction projects is highly affected by the competences of the project manage. It is found that the top three measures of construction employees’ performance according to its influence by the competencies of the projects managers are; â€˜productivityâ€™, â€˜compliance with work instructionsâ€™ and â€˜working after regular working timeâ€™. Whereas to influence the employees’ performance, the top three most important competencies needed for project manager were : â€˜communication skillsâ€™, â€˜team managementâ€™ and â€˜problem solvingâ€™. The best methods to develop the project manager’s competencies are â€˜on-the job trainingâ€™, â€˜off-the job trainingâ€™ and â€˜Observing experienced othersâ€™.